Management of Facilities and Infrastructure in Islamic Boarding Schools - Gina Febriana (Konsultan Jurnal Ilmiah Indonesia, 2024)
The implementation of education cannot be separated from facilities and infrastructure. Facilities and infrastructure are important supporting elements in the education process to achieve educational goals. Therefore, Law of the Republic of Indonesia Number 20 of 2003 concerning the National Education System, Chapter XII, Article 45, educational units are required to fulfill educational facilities and infrastructure. Educational institutions with a pesantren style have certain advantages but also have their own weaknesses. The method used in this article is a type of qualitative research with library research, namely research whose subjects are library literature. The results of this research are that the process of managing educational facilities and infrastructure that runs well will be one of the efforts to overcome the weaknesses that are generally experienced in the world of pesantren, so that pesantren can develop further by implementing good management.